Evaluation of a single‐administration ototopical treatment for canine otitis externa: a randomised trial. Issue 1 (14th November 2017) - Blake, John; Keil, Daniel; Kwochka, Kenneth; Palma, Kathleen; Schofield, Jennifer
Abstract : Objective: To evaluate the efficacy and safety of a new, single‐administration Otic Solution containing florfenicol, terbinafine and mometasone furoate for the treatment of canine otitis externa (OE). Design: The clinical efficacy and safety study was a multicentre, controlled, masked and randomised field study conducted over 30 days. Two hundred and twenty‐one (221) client‐owned dogs of varying breeds with diagnosed bacterial and/or fungal OE were enrolled. Procedure: Dogs were randomised to either Otic Solution or control groups. Evaluations were conducted over a minimum period of 30 days with a primary effectiveness endpoint based on the improvement in a clinical severity score at the final visit (day 30). Safety analyses were based on clinical and laboratory parameters and the occurrence of adverse events. Results: The Otic Solution group demonstrated a significantly higher treatment success rate compared with that observed for the control group (72.5 per cent v 11.1 per cent, P value=0.0001) for cases of OE caused by Staphylococcus pseudintermedius and Malassezia pachydermatis. No significant safety findings were reported. Conclusions/clinical relevance: This new ototopical formulation provides safe and effective treatment of canine OE and is an important alternative antimicrobial for this indication. The single‐administration dosage regimen eliminates opportunities for client dosage administration errors and medication stockpiling.